2020
DOI: 10.32604/cmes.2020.010869
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Forgery Detection in Image Frames of the Videos Using Enhanced Convolutional Neural Network in Face Images

Abstract: Different devices in the recent era generated a vast amount of digital video. Generally, it has been seen in recent years that people are forging the video to use it as proof of evidence in the court of justice. Many kinds of researches on forensic detection have been presented, and it provides less accuracy. This paper proposed a novel forgery detection technique in image frames of the videos using enhanced Convolutional Neural Network (CNN). In the initial stage, the input video is taken as of the dataset an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Background subtraction (BGS) serves as the primary and crucial stage for human detection in image, and it is utilized further for feature extraction purposes. Several BGS techniques have been suggested previously, such as self-organizing maps, statistical methods, temporal, and feature-based methods [21]. However, BGS methods usually rely on color spaces, such as RGB, YUV, and HSV that include limitations of color camouflage and lighting changes.…”
Section: Rgb-d Image's Silhouette Extraction Using Depth Silhouettesmentioning
confidence: 99%
“…Background subtraction (BGS) serves as the primary and crucial stage for human detection in image, and it is utilized further for feature extraction purposes. Several BGS techniques have been suggested previously, such as self-organizing maps, statistical methods, temporal, and feature-based methods [21]. However, BGS methods usually rely on color spaces, such as RGB, YUV, and HSV that include limitations of color camouflage and lighting changes.…”
Section: Rgb-d Image's Silhouette Extraction Using Depth Silhouettesmentioning
confidence: 99%
“…It was proved that the accuracy of the gesture analysis of this model was 11.6~24.0% higher than that of the machine learning model. Velliangiri et al [13] designed an automatic detection model that combined CNN and crow search algorithms to solve false-frame recognition in video images. The test results showed that the method had a false-frame-recognition accuracy of 97.21% on the experimental dataset, which was higher than the other existing methods.…”
Section: Related Workmentioning
confidence: 99%
“…This step recognizes the Braille cells based on an end-to-end DCNN model due to its ability to learn image features better than traditional methods for image feature extraction [25][26][27][28]. Moreover, DCNN models have achieved high accuracy results compared with other deep learning models for several computer vision-based tasks [29].…”
Section: Braille Cell Recognitionmentioning
confidence: 99%